Using RDP with IBM FlashSystem to debug fibre channel optics errors - Jagdale, Ashish; Chitlange, Mohit M. (IBM Redbooks, 2022)
The focus of this IBM® blueprint is to showcase the Read Diagnostic Parameters (RDP) feature of the Fibre Channel protocol (FCP). The data that is provided by RDP commands can simplify the process of managing and analyzing any issues on complex SAN fabrics. In this blueprint, we provide guidance to help users and administrators understand the meaning of RDP data and how to use it. The intent of this blueprint is to help a user understand what RDP is, what data RDP represents, and how to use that data to identify potential issues within the SAN fabric that is hosted by that Fibre Channel (FC) switch.